Comparing Ionospheric MUF using IRI16 Model with Mid-Latitude Ionosonde Observations and Associated with Strong Geomagnetic Storms - Al-Shallal, Ala’a A.; Al-Ubaidi, Najat M. R. (Iraqi Journal of Science, 2020)
High frequency (HF) radio wave propagation depends on the ionosphere status which is changed with the time of day, season, and solar activity conditions. In this research, ionosonde observations were used to calculate the values of maximum usable frequency (MUF) the ionospheric F2- layer during strong geomagnetic storms (Dst â‰¤ -100 nT) which were compared with the predicted MUF for the same layer by using IRI-16 model. Data from years 2015 and 2017, during which five strong geomagnetic storms occurred, were selected from two Japanese ionosonde stations (Kokubunji and Wakkanai) located at the mid-latitude region. The results of the present work do not show a good correlation between the observed and predicted MUF values for F2- layer during the selected events of strong geomagnetic storms at these stations. Thus, there is a further need to improve the IRI-16 model for better matching with the observations during strong geomagnetic storms.